IMPLEMENTASI SUPERVISI MANAJERIAL DAN KOLABORATIF DALAM PENGEMBANGAN PROFESIONAL GURU: STUDI KASUS DI SMP KIFAYATUL AHYAR BANDUNG - Syahida Zawaliyah; Mulyawan Safwandy Nugraha (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT School supervision is an important strategy for improving teacher professionalism; however, its implementation is often dominated by administrative compliance rather than continuous professional development. This study aims to analyze the implementation of managerial and collaborative supervision in supporting teacher professional development at SMP Kifayatul Ahyar, Bandung City, and to formulate an integrative supervision model as an effort to strengthen teacher development practices. This study employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving school managerial staff, teachers, and administrative personnel. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings reveal that managerial supervision has been implemented regularly and systematically with digital support, but it remains primarily focused on evaluating instructional administration. Collaborative supervision has begun to develop through teacher discussions and learning evaluations; however, it has not yet been systematically organized into a professional learning community. Furthermore, supervision data have not been optimally utilized as a basis for teacher professional development planning. This study proposes an integrative supervision model that combines managerial, collaborative, and data-based approaches through five stages: administrative audit, pedagogical observation, collaborative reflection, supervision data analysis, and professional follow-up. The proposed model is expected to strengthen the role of supervision as a sustainable strategy for improving teaching quality and supporting continuous teacher professional growth. ABSTRAK Supervisi sekolah merupakan salah satu strategi penting dalam meningkatkan profesionalisme guru, tetapi implementasinya masih sering berorientasi pada pemenuhan aspek administratif dibandingkan pengembangan kompetensi profesional secara berkelanjutan. Penelitian ini bertujuan menganalisis implementasi supervisi manajerial dan supervisi kolaboratif dalam mendukung pengembangan profesional guru di SMP Kifayatul Ahyar, Kota Bandung, serta merumuskan model supervisi integratif sebagai upaya penguatan kualitas pembinaan guru. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara semi-terstruktur, observasi non-partisipatif, dan studi dokumentasi yang melibatkan unsur kepala sekolah, guru, dan administrasi sekolah. Analisis data dilakukan menggunakan model interaktif Miles, Huberman, dan Saldaña melalui tahapan reduksi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa supervisi manajerial telah terlaksana secara rutin dan terstruktur dengan dukungan sistem digital, tetapi masih dominan pada pemeriksaan administrasi pembelajaran. Supervisi kolaboratif mulai berkembang melalui diskusi dan evaluasi pembelajaran, namun belum terorganisasi dalam bentuk komunitas belajar profesional. Selain itu, data hasil supervisi belum dimanfaatkan secara optimal sebagai dasar perencanaan pengembangan profesional guru. Penelitian ini menghasilkan model supervisi integratif yang menggabungkan aspek manajerial, kolaboratif, dan berbasis data melalui tahapan audit administrasi, observasi pedagogik, refleksi kolaboratif, analisis data, dan tindak lanjut profesional. Model ini diharapkan dapat memperkuat peran supervisi sebagai instrumen peningkatan mutu pembelajaran yang berkelanjutan.